Changing trends in the epidemiology of vertebral osteomyelitis in Marseille, France. (September 2015) - Doutchi, Mahamadou; Seng, Piseth; Menard, Amélie; Meddeb, Line; Adetchessi, Tarek; Fuentes, Stephane; Dufour, Henry; Stein, Andreas
Abstract: The incidence and significant morbidity of vertebral osteomyelitis are increasing despite the progress of diagnosis competences. Among the 50 cases of vertebral osteomyelitis managed in our centers over the past 5 years, 84% of the cases were in men. The mean age was 55 years. Sixty-two percent of patients had comorbidities and risk factors: diabetes mellitus (24%), malignancy (16%), intravenous drug use (10%) and alcoholism (4%). A source of infection was identified in 66% of cases, including postvertebral surgery infection (18%) and hematogenous infection (48%). The mean time to diagnosis was 36 days. Back pain were occurred in 90% of cases, fever (70%), neurologic deficits (40%), epidural abscesses (32%), completed vertebral bone destruction (26%) and psoas abscess (12%). A single organism was isolated in 92% of cases. Gram-positive bacteria were identified in 76% of cases, while Gram-negative bacilli (GNB) were found in 18% of cases. The presence of GNB was significantly associated with malignancy (p 0.041). The mean duration of antibiotic therapy was 123 days. Surgical treatment was performed in 41 cases: spinal stabilization (26%), drainage of abscesses (32%) and relief of compression (40%). Residual pain was found in 24% of cases, and neurologic sequelae in 22%. Cervical or thoracic localization was a risk factor for neurologic compromise (p 0.042). The epidemiology of vertebral osteomyelitis has changed; an increase in malignancy that was significantly associated with vertebral osteomyelitis due to GNB has been observed. Our study shows that the rate of neurologic complications remains high despite improved diagnostic capabilities and optimal treatment.